Heaven and Earth Are Not Humane : the Problem of Evil in Classical Chinese Philosophy. - Perkins, Franklin (World philosophies., 2014)
That bad things happen to good people was as true in early China as it is today. Franklin Perkins uses this observation as the thread by which to trace the effort by Chinese thinkers of the Warring States Period (c.475-221 BCE), a time of great conflict and division, to seek reconciliation between humankind and the world. Perkins provides rich new readings of classical Chinese texts and reflects on their significance for Western philosophical discourse.